CONFLICT LOGICAL COMPETENCE OF THE MARRIED COUPLE IN RESOLVING FAMILY CONFLICTS - Balakhtar, Valentyna; Voloshyna, Yuliia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
Abstract The relevance of the study is determined by the need to resolve family conflicts as significant psychological problems that require resolution and cause activity of spouses aimed at overcoming contradictions or disputes in the family caused by various reasons. Solving conflicts in a married couple in today's crisis conditions by forming the family's conflict-related competence is especially in demand in the context of solving the researched problem. The purpose of the article is to determine the level of conflict-related competence and the significance of the properties of the conflict-competent behavior of spouses in resolving family conflicts. The research used a complex of theoretical methods of scientific knowledge (analysis, synthesis - allowed to characterize the main concepts of the research, analyze scientific sources; systematization and generalization - to formulate conclusions) and empirical (methodology “Assessment of the level of competence in conflict resolution”, etc.). The sample consisted of 65 people, who were divided into groups depending on age, gender, place of residence, years of married life, and the number of children in the family. The results of an empirical study of conflict competence of spouses are given. An insufficient level of its formation was revealed in more than half of the respondents (low). According to the results of dispersion analysis, statistically, significant features of conflict competence were found depending on gender (men are more competent compared to women), place of residence (men in rural areas are characterized by higher indicators compared to men living in the city and women, regardless of the place of residence), the number of children in the family (the highest indicators of competence were found in men in families with 1 child and women in families with 2 children), years of married life (women are the most capable of resolving family conflicts, who have been married for more than 10 years and men from families with 5-10 years of experience) and others. The need to develop and approve a program to promote the formation of conflict-related competence of spouses is seen as promising